AB1056 THE EXPERIENCES OF BIOLOGICAL THERAPIES IN CHILDREN WITH JUVENILE IDIOPATHIC ARTHRITIS ASSOCIATED UVEITIS, SINGLE CENTER STUDY. (June 2019) - Sözeri, Betül; Kardes, Esra; Demir, Ferhat; Ciftci, Fatma; Demircioglu, Zeynep
Abstract : Background: Juvenile idiopathic arthritis (JIA) is the most common systemic disease causing uveitis in childhood, with a prevalence of 10 per 100 000 persons. JIA-associated uveitis is estimated to have a poor prognosis and has a high rate of complications. JIA-associated uveitis can manifest in various forms, depending on the location and severity of the ocular inflammation, as well as on the type of arthritis. The most of JIA patients with uveitis have oligoarthritis. Therefore, other types of JIA are rarely accompanied by uveitis. Topical corticosteroids are the first line therapy, and disease conventional and biologic modifying anti-rheumatic drugs (DMARDs) are used. Objectives: The purpose of the present study was to report on the clinical characteristics, ocular complications, treatment, and visual outcome in children with JIA-associated uveitis who were examined in recent years at a single tertiary pediatric rheumatology and ophthalmology center in Turkey. Methods: We retrospectively analyzed the data of 41 JIA patients (14 males, 27 females). The duration between the initial evaluation and the final visit was recorded as follow-up time. Juvenile idiopathic arthritis was defined according to the International League of Associations for Rheumatology (ILAR) classification criteria. Uveitis was classified according to the SUN classification. Two approaches were utilized to evaluate the change of visual acuity (VA) during the disease course: (i) VA was measured on Snellen chart. The equivalent logarithm of the minimum angle of resolution acuity (logMAR) was calculated and used for analysis. Results: The study included 31 patients (57 eyes) of whom 22 (71%) were females. Mean age (±SD) at uveitis diagnosis was 8.42 (±4.13) years (median 8, range: 34 month–17 years) and there was no significant difference between genders. The mean age at jia diagnosis was 8.42 (±4.7), respectively. Nine patients were ≤ 7 years of age at the time of JIA diagnosis. Anterior uveitis (AU) was the most common type, diagnosed in 57 (76%) eyes. All patients had methotrexate, therefore biologic therapy was used in 29/31 patients (93.5%) at the follow up time (infliximab in 12, adalimumab in seventeen, and tocilizumab in three patients) and 9 children (31%) required ≥2 biologics over the follow up period. Thirteen patients switched between infliximab and adalimumab (10 patients switched from infliximab). The reason for treatment switch included treatment failure and treatment-related side-effects (n=3). Systemic and topical steroids treatment were gradually tapered and discontinued in all patients after initiation of biologics. Of the all affected eyes, posterior synechiae (n=24) was the predominant complication on presentation. During the follow-up period new complications were seen in 11 eyes (13%). Posterior synechiea (6 eyes, 7, 5%) was the most frequent complication observed followed by cataract (3 eyes, 3, %) and glaucoma (2 eyes, 2, 5%) Improvement or preservation of visual acuity (VA) was noted in 77 eyes (%94, 3) at the last visit. Conclusion: We report a large cohort of children with JIA uveitis managed in a Turkey tertiary unit. Low complication rates and favorable visual outcomes are found in the present study. The high rate of biologic use), and close monitoring of affected children with pediatric rheumatology and uveitis clinic may have contributed to our improved outcomes. Disclosure of Interests: None declared